Sistem Pendukung Keputusan Untuk Menentukan Stok Kue Menggunakan Forward Chaining Di Toko Cookies YARR - Nurul Fajrina; Mufida Khairani; Yessi Fitri Annisah Lubis (Unit Pengelola Jurnal Universitas Harapan Medan, 2023)
Advances in information and communication technology make it easier for humans to manage data and information, so there is no need to waste a lot of time, effort and money. Technology is useful in various fields, one of which is in the field of small business economics, namely sales stock. In order to make it easier for the owner to make incoming and outgoing stock reports, it is necessary to implement computerized sales data in one web application, which includes information on incoming and outgoing stock of cookies that are still available at the YARR Cookies shop. Stages in Decision Support System research using the Forward Chaining method which will collect facts and end with conclusions. And the end result of this web application can be run properly and is also useful for the owner of the YARR cookie shop.